Spatial and Temporal Profile of Glycine Betaine Accumulation in Plants Under Abiotic Stresses - Annunziata, Maria Grazia; Ciarmiello, Loredana Filomena; Woodrow, Pasqualina; Dell’Aversana, Emilia; Carillo, Petronia (Frontiers in Plant Science, 2019)
Several halophytes and a few crop plants, among which Poaceae, synthesize and accumulate glycine betaine (GB) in response to environmental constraints. GB has an important role in osmoregulation, in fact, it is one of the main nitrogen-containing compatible osmolytes found in Poaceae. It can interplay with molecules and structures preserving the activity of macromolecules, maintaining the integrity of membranes against stresses and scavenging ROS. Exogenous GB applications have been proved to induce the expression of genes involved in oxidative stress responses, with a restriction of ROS accumulation and lipid peroxidation in cultured tobacco cells under drought and salinity, even stabilizing photosynthetic structures under stress. In the plant kingdom, GB is synthesized from choline by two-step oxidation reactions. The first oxidation is catalyzed by choline monooxygenase (CMO) and the second oxidation is catalyzed by NAD+-dependent betaine aldehyde dehydrogenase (BADH). Moreover, in plants, the cytosolic enzyme, named N-methyltransferase (PEAMT), catalyzes the conversion of phosphoethanolamine to phosphocholine. However, changes in CMO expression genes under abiotic stresses have been observed. GB accumulation is ontogenetically controlled since it happens in young tissues during prolonged stress, while its degradation is generally not significant in plants. This ability of plants to accumulate high levels of GB in young tissues under abiotic stresses is independent of nitrogen (N) availability and supports the view that plant N allocation is dictated primarily to supply and protect the growing tissues even under N limitation. Indeed, the contribution of GB to osmotic adjustment and ionic and oxidative stress defense in young tissues is much higher than that in older ones. In this review, the biosynthesis and accumulation of GB in plants under several abiotic stresses are analyzed focusing the attention on all the possible roles this metabolite can play, in particular in young tissues.